RESERVOIR CHARACTERIZATION AND FACIES ANALYSIS OF KEUTAPANG FORMATION, RAJA FIELD, NORTH SUMATRA - Lee Lumban Raja, David
Raja Field is one of the oil fields in the North Sumatra Basin. Administratively Raja Field located in Rantau Sub-District, Aceh Tamiang District, Aceh Province. The field consists of Keutapang Formation and Seurula Formations. The study was conducted on Keutapang Formation to determine the facies of deposition environments and the character of the two reservoirs found on this Raja Field, Reservoir A at a depth of about 400 m below sea level and Reservoir B at a depth of about 550 m below sea level. The data used in this research are core data, wireline log data, 3D seismic data, and production history data. The results of core analysis show that Reservoir A consists of massive sandstone lithology which is interpreted as upper shoreface sedimentary sandstone, while Reservoir B consists of shaly sandstone lithology that is interpreted as lower shoreface deposit. The results of ichnofossil analysis found in core indicate Reservoir B is a litoral zone deposit - sandy shore deposit. The determination of the petrophysical character uses wireline log data. Petrophysical characters analyzed were effective porosity, water saturation, and shale volume. Reservoir A shows an average effective porosity of 17%, average shale volume 22%, and average water saturation of 68%, while Reservoir B shows an average effective porosity of 14%, average shale volume 26% and water saturation averaged 76%.